Prevalence and trends of coexisting forms of malnutrition and its associated factors among children aged 6–59 months in South and Southeast Asia, 1996–2022: a cross-sectional time series study - Wenjie Guo; Maggie Zgambo; Sanmei Chen; Yoko Shimpuku (BMC Public Health)
Abstract Background South and Southeast Asia face severe malnutrition in children under five, with coexisting forms of malnutrition (CFM) exacerbating mortality risks and posing greater challenges than isolated forms of malnutrition. We aimed to assess the prevalence, trends, and factors of CFM among children aged 6–59 months in South and Southeast Asian countries and the entire region. Methods We used anthropometric and hemoglobin data from 515,170 children aged 6–59 months in seven low- and middle-income South and Southeast Asian countries, based on Demographic and Health Surveys conducted between 1996 and 2022. Weighted multivariable logistic regression was performed to identify the sociodemographic factors associated with seven forms of CFM: coexistence of underweight with wasting, coexistence of underweight with stunting, coexistence of underweight with both wasting and stunting, coexistence of stunting with overweight/obesity (CSO), coexistence of anemia with overweight/obesity, coexistence of anemia with underweight, and coexistence of anemia with stunting (CAS). Results The overall pooled prevalence of child CFM ranged from 0.8% for CSO to 23.4% for CAS. Most countries showed a declining trend in CFM, except for Timor-Leste, India, and the Maldives. Higher maternal education and being male were associated with lower odds of CFM. Compared to children aged 6–23 months, those aged 24–59 months had a higher risk of CUS but a lower risk of CSO and CAO. Children in India had higher odds of experiencing CAU and CAS compared to those in the Maldives, Myanmar, Nepal, and Timor-Leste. Conclusion The coexistence of undernutrition and/or anemia in South and Southeast Asia remains a public health problem. Although the prevalence of child CFM has decreased in most countries, it remains higher in Timor-Leste and India. It is necessary to consider multi-faceted nutritional interventions for children with CFM in this region, taking into account the impact of children’s gender, age, and maternal education, to further reduce child CFM.